Interpretation in Character Education Student (Munasabah approach of the Quran) - Bisyri Abdul Karim; Akhmad Syahid; Rosmiati Rosmiati; Martini Martini (AL-ISHLAH: Jurnal Pendidikan, 2023)
This research examines the concept of interpretation in student character education with the Qur'an munasabah approach  . The purpose of the study will  analyze the concept of character education and interpretation of the themes of character education contained in the Qur'an which can be used as a reference for planting and transmitting student character education in higher education.  Based on the results of the analysis, it can be concluded that student character education  is a process of instilling good character values as a conscious effort through education. This process is carried out continuously as a planned stage of transmission to equip students with noble personalities. Reference sources related to student character education can be explored in the verses of the Qur'an with a munasabah  approach to absorb the meaning of verses related to character education including verses themed on honesty character, disciplinary, hard work, curiosity, achievement, friendliness, peace-loving, reading character  , and social character of college students.